Perfil ocupacional e exposição a agrotóxico e nicotina de trabalhadores da área rural de Arapiraca – AL envolvidos no cultivo do tabaco - Silva, Francisca Maria Nunes da (2011)
The pesticides are chemical substances used to control pests or diseases of plants and animals. Used since classic Greece, these products were spread in several countries after Second World War and in Brazil starting from the decade of 60. Now Brazil is the largest pesticides consumer in the world. The inadequate use of pesticides has been a problem for human and environmental health. Especially the agricultural workers are exposed to the harmful effects of these products. In tobacco farming, in association to the problems caused by exposure to pesticides, farm workers are still exposed to the intoxication caused by nicotine in the tobacco leaf. In Arapiraca, important tobacco producer on the national scenery, the culture of tobacco stands out for excessive pesticides use, a fact that contributes to occurrence of health hazards to workers, mainly for the inappropriate working conditions and disregard for safety standards. This study aimed to characterize the occupational profile of the tobacco growers of Arapiraca, Alagoas, and their exposure to pesticide and nicotine. This is a cross-seccional descriptive study, where 70 workers of the cultivation of the tobacco were interviewed, being used a semi-structured questionnaire to obtain information concerning the occupational profile. The results showed that 41,4% of the workers interviewees ranged in age from 30-45 years and 55,7% had incomplete primary education or were illiterate. It was also observed that 37,1% were owners of the rural property and 58% an income per capita up to a quarter of minimum wage. Almost half of rural workers (47,1%) began work in the tobacco farming until the age of 8 and 48,6% were between 11-30 years of work Most, 54,3% told to work up to 8 hours/day, and 61% worked six days of the week. Also most of the workers (62,9%), applied pesticides and 43,2% of these spent between 5-8 hours a day in the application. Manual backpack pulverizer was used by 72,7% of the pesticide applicators. Among the pesticides used, Confidor was the most mentioned. Regarding the use of protection measures during the mixture of pesticides, 56,8% didn't use none measure and 34,1% justified due to high cost. Most washed hands (93,2%) and took a shower 79,5% often immediately after applying pesticide. Two-thirds of the workers (61,3%) never drank liquid during the application of pesticides and 75% never ate during the same procedure. While 40,9% of the interviewees gotten sick after the pesticides application, 72,7% reported not having pesticide poisoning. Headache, nausea and vomit were signs and symptoms more referred. Regarding exposure to nicotine, 84,3% of the respondents reported skin contact with the tobacco leaf and 71,5% had such contact ever. The use of gloves during harvesting and washing of hands after the harvest was reported by 57,1% e 85,7% of employees, respectively. Most growers (64,3%) had felt ill during the harvest and symptoms most often reported were headache, vomiting and nausea. Most workers, 58,6%, was not smoker and 51,4% didn't smoke while handling the tobacco leaf. It is concluded from this study that growers are constantly exposed to the effects of nicotine and pesticides due to long working hours, poor adherence to prevention available tecnologies due to vulnerabilities and risk minimization.